Hermenêutica e educação campesina - As contribuições de Paul Ricoeur para o ensino de filosofia na Escola Estadual Agrícola David Aires França - Gomes, Maristela Firmino da Cunha (Universidade Federal do Tocantins, 2021)
The perspective of this work was to make an analysis on a practice in Philosophy Teaching given at Escola Girassol de Tempo Integral Agrícola David Aires França, located in the rural area of the City of Arraias - TO, aiming to investigate the contributions and from them, the searches for integrate Philosophy Teaching in a rural school, as a process of belonging, which leads to the acquisition of knowledge and recognition of the self, the other and their cultural context in the process of Education of thought, in the light of the hermeneutical theory of Jean Paul Gustave Ricoeur ). The study aims to integrate thought and practice, considering PROF-FILO as a Postgraduate Program that points out issues that emphasize the interlocution of the praxis of a research with its destiny: The school floor in the process of building knowledge in everyday life of the classroom. In the first chapter, A Philosophical Perspective of Hermeneutics in Education Paul Ricoeur presents the main influences on education that Paul Ricoeur produced in contemporary hermeneutic thought. It is demonstrated how he brought to the scene theories such as pragmatics and hermeneutics that, today, figure as protagonists on the scene of the philosophical world. Based on the philosophical foundations that paved the way for philosophical hermeneutical thinking in education, in the second chapter, The Teaching of Philosophy in Peasant Education in the Light of Paul Ricoeur's Thought, a historical abbreviated presentation on the challenges for implementing peasant education and Philosophy teaching in Brazil and the importance of Ricouerian hermeneutics in this context. In the third and last chapter, the role of a peasant school in promoting autonomy, social justice and human dignity is addressed, through a practice of openness to a dialectical perspective, in a dialogical process in which the student is asked to inquire, criticize, create, reflect and act. Also noteworthy are the relationships developed at the school, the mediations and experiences of the entities that compose it and build the entity: Escola Estadual Girassol de Tempo Integral Agrícola David Aires França.